Tethered dithiacyclopropenones: syntheses and structural properties of tetrathiacyclopropenonophanes - Werz, Daniel B.; Rominger, Frank; Hyla-Kryspin, Isabella; Gleiter, Rolf (The journal of organic chemistry, 2001)
The reaction of the cyclic tetrathiadiynes 4(m.n) (where m and n indicate the number of methylene groups between the dithiaacetylene units) with sodium trichloroacetate and subsequent hydrolysis of the gem-dichlorocyclopropenes afforded the mono- and biscyclopropenone derivatives 5(m.n) and 6(m.n) in moderate yields. Investigation of the X-ray crystal structures revealed small torsion angles between the CH2−S bond and the C−C double bond, indicating conjugation between the sulfur 3p lone pair and the cyclopropenone ring. The maintenance of the conjugation determines the secondary structure of both (5, 6) ring systems.